2011
DOI: 10.1007/s12520-011-0069-9
|View full text |Cite
|
Sign up to set email alerts
|

Damage caused by insects during the mummification process: an experimental study

Abstract: The process of mummification had been known since the Fourth Dynasty of the Old Kingdom (ca. 2600 BC) and continued to develop throughout ancient Egyptian history. Although mummification protected the body from decay, especially by microbes, some mummification techniques left the body susceptible to insect attack. Certain types of insects have been detected in the mummies. In scholarly publications, most authors have dealt with microorganisms, while few have concerned themselves in depth with the effect of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 30 publications
(31 reference statements)
1
14
0
Order By: Relevance
“…2A) as a flexible support for the paint layers and it is characteristic with ribbon-twisted structure that is remarkable to cotton fibers [26,27]. The fibers appear randomly with good distribution of the filler and the distance between fibers is very close [28]. There are tears due to the natural aging of fibers.…”
Section: Resultsmentioning
confidence: 99%
“…2A) as a flexible support for the paint layers and it is characteristic with ribbon-twisted structure that is remarkable to cotton fibers [26,27]. The fibers appear randomly with good distribution of the filler and the distance between fibers is very close [28]. There are tears due to the natural aging of fibers.…”
Section: Resultsmentioning
confidence: 99%
“…1). The mummies in the late period were characterized by the extensive use of resin in the body cavities, and there was more concern with the external appearance than the preservation of the body [2,5,14]. Intact fiber, powder fiber, and small bone (lumbar vertebra) samples were taken from the studied mummy.…”
Section: Archaeological Mummymentioning
confidence: 99%
“…Egyptian civilization is one of the earliest in history, and the ancient Egyptians recorded not only their writings but also their memories through mummification of their bodies. The ancient Egyptians believed in resurrection after death and made it necessary to preserve their bodies to the afterlife [1][2][3][4][5]. The mummification (artificial mummification) was practiced in Egypt from the Old Kingdom to the Christian era.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be because softer materials such as paper and wood were more readily available, as providing pupation substrates is a common practice in the management of dermestid laboratory colonies to minimise mortality due to cannibalism (Fontenot et al 2015). Experimental studies on mummified rats in Egypt have shown conclusively that dermestid larvae excavate pupation chambers in dried tissues and bone (Abdel-Maksoud et al 2011). Dermestid pupal chambers usually occur in clusters and, when they appear on bones, may indicate a situation of stress with limited availability of both food and pupation substrates (Roberts et al 2003).…”
Section: Dermestid Beetlesmentioning
confidence: 99%